The excess costs of depression: a systematic review and meta-analysis - König, H.; König, H.-H.; Konnopka, A. (Epidemiology and psychiatric sciences, 2019)
Major depressive disorders are highly prevalent in the world population, contribute substantially to the global disease burden and cause high health care expenditures. Information on the economic impact of depression, as provided by cost-of-illness (COI) studies, can support policymakers in the decision-making regarding resource allocation. Although the literature on COI studies of depression has already been reviewed, there is no quantitative estimation of depression excess costs across studies yet. Our aims were to systematically review COI studies of depression with comparison group worldwide and to assess the excess costs of depression in adolescents, adults, elderly, and depression as a comorbidity of a primary somatic disease quantitatively in a meta-analysis. We followed the PRISMA reporting guidelines. PubMed, PsycINFO, NHS EED, and EconLit were searched without limitations until 27/04/2018. English or German full-text peer-reviewed articles that compared mean costs of depressed and non-depressed study participants from a bottom-up approach were included. We only included studies reporting costs for major depressive disorders. Data were pooled using a random-effects model and heterogeneity was assessed with I2 statistic. The primary outcome was ratio of means (RoM) of costs of depressed v. non-depressed study participants, interpretable as the percentage change in mean costs between the groups. We screened 12 760 articles by title/abstract, assessed 393 articles in full-text and included 48 articles. The included studies encompassed in total 55 898 depressed and 674 414 non-depressed study participants. Meta-analysis showed that depression was associated with higher direct costs in adolescents (RoM = 2.79 [1.69-4.59], p < 0.0001, I2 = 87%), in adults (RoM = 2.58 [2.01-3.31], p < 0.0001, I2 = 99%), in elderly (RoM = 1.73 [1.47-2.03], p < 0.0001, I2 = 73%) and in participants with comorbid depression (RoM = 1.39 [1.24-1.55], p < 0.0001, I2 = 42%). In addition, we conducted meta-analyses for inpatient, outpatient, medication and emergency costs and a cost category including all other direct cost categories. Meta-analysis of indirect costs showed that depression was associated with higher costs in adults (RoM = 2.28 [1.75-2.98], p < 0.0001, I2 = 74%). This work is the first to provide a meta-analysis in a global systematic review of COI studies for depression. Depression was associated with higher costs in all age groups and as comorbidity. Pooled RoM was highest in adolescence and decreased with age. In the subgroup with depression as a comorbidity of a primary somatic disease, pooled RoM was lower as compared to the age subgroups. More evidence in COI studies for depression in adolescence and for indirect costs would be desirable.